KONSEP BERKAH DALAM PERSPEKTIF TAFSIR - Rama Satria; Alimron; Abdurrazaq (CV. Adiba Aisha Amira, 2023)
This research aims to find out how to seek God's blessings in the Qur'an. There are five ways to seek God's blessings contained in the Qur'an based on the interpretation of blessing verses. First, following the instructions of the Qur'an, where the Qur'an itself is a holy book full of blessings, there are many blessing verses associated with the Qur'an, that the Qur'an itself has unlimited blessings. the form of blessing, starting from the arrangement of the words, the content of the verses of the Qur'an to the place and time when the Qur'an was revealed, the way to seek blessings with the Qur'an is to recite the verses of the Qur'an. Second, faith and piety, based on the interpretation of the blessing verses, faith and piety are absolute requirements that a person must have in order to have a life full of blessings. Third, patience, it is said that Allah gave abundant blessings to the followers of the Prophet Moses because of their patience. Fourth, Say hello. Fifth, Hijrah and prayer. Barakāh is Ziyādatul Khair which means increasing goodness. Barakāh can also mean the persistence of something, and can also mean the increase or development of something. The blessings described in the Qur'an can be in the form of a fertile and prosperous land, there are also depictions of blessings in the Qur'an, etc. This research wants to know how to find God's blessings in the Qur'an, by examining blessing verses. The research method used to find out these two things is a qualitative research method, while the source of research data is interpretations of the Al-Qur'an and other related sources. The interpretation method used in this research is the thematic interpretation method, namely the interpretation method that interprets the Al-Qur'an based on a certain theme, in this case the interpretation of blessings.